What Constitutes an Ideal Dental Restorative Material?. (November 2013) - Rekow, E.D.; Bayne, S.C.; Carvalho, R.M.; Steele, J.G.
Intense environmental concerns recently have prompted dentistry to evaluate the performance and environmental impact of existing restoration materials. Doing so entices us to explore the 'what if?' innovation in materials science to create more ideal restorative materials. Articulating a specification for our design and evaluation methods is proving to be more complicated than originally anticipated. Challenges exist not only in specifying how the material should be manipulated and perform clinically but also in understanding and incorporating implications of the skill of the operator placing the restoration, economic considerations, expectations patients have for their investment, cost-effectiveness, influences of the health care system on how and for whom restorations are to be placed, and global challenges that limit the types of materials available in different areas of the world. The quandary is to find ways to actively engage multiple stakeholders to agree on priorities and future actions to focus future directions on the creation of more ideal restorative materials that can be available throughout the world.